Increasing Nerve Autograft Length Increases Senescence and Reduces Regeneration. Issue 4 (October 2018) - Hoben, Gwendolyn M.; Ee, Xueping; Schellhardt, Lauren; Yan, Ying; Hunter, Daniel A.; Moore, Amy M.; Snyder-Warwick, Alison K.; Stewart, Sheila; Mackinnon, Susan E.; Wood, Matthew D.
Abstract : Background: Nerve grafting with an autograft is considered the gold standard. However, the functional outcomes of long (>3 cm) nerve autografting are often poor. The authors hypothesized that a factor contributing to these outcomes is the graft microenvironment, where long compared to short autografts support axon regeneration to different extents. Methods: A rat sciatic nerve defect model was used to compare regeneration in short (2 cm) and long (6 cm) isografts. Axon regeneration and cell populations within grafts were assessed using histology, retrograde labeling of neurons regenerating axons, immunohistochemistry, quantitative reverse transcriptase polymerase chain reaction, and electron microscopy at 4 and/or 8 weeks. Results: At 8 weeks, for distances of both 1 and 2 cm from the proximal coaptation (equivalent regenerative distance), long isografts had reduced numbers of regenerated fibers compared with short isografts. Similarly, the number of motoneurons regenerating axons was reduced in the presence of long isografts compared with short isografts. Considering the regenerative microenvironments between short and long isografts, cell densities and general populations within both short and long isografts were similar. However, long isografts had significantly greater expression of senescence markers, which included senescence-associated β-galactosidase, p21, and p16, and distinct chromatin changes within Schwann cells. Conclusions: This study shows that axon regeneration is reduced in long compared with short isografts, where long isografts contained an environment with an increased accumulation of senescent markers. Although autografts are considered the gold standard for grafting, these results demonstrate that we must continue to strive for improvements in the autograft regenerative environment.